Preparation and characterization of gatifloxacin-loaded sodium alginate hydrogel membranes supplemented with hydroxypropyl methylcellulose and hydroxypropyl cellulose polymers for wound dressing - Prabu, Durai (2016)
Introduction: The aim of this study is to evaluate gatifloxacin-loaded sodium alginate hydrogel membranes, supplemented with glycerol (a plasticizer), glutaraldehyde (a cross-linking agent), and hydroxypropyl methylcellulose (HPMC) or hydroxypropyl cellulose (HPC) polymers, as potential wound dressing materials based on their physicochemical properties and the sustain-release phenomenon. Materials and Methods: The physicochemical properties of the prepared hydrogel membranes were evaluated by several methods including Fourier transform infrared and differential scanning calorimetry. Different techniques were used to assess the swelling behavior, tensile strength and elongation, % moisture absorption, % moisture loss, water vapor transmission rate (WVTR), and microbial penetration for the hydrogel membranes. In vitro gatifloxacin release from the hydrogel membranes was examined using the United States Pharmacopeia XXIII dissolution apparatus. Four kinetics models (zero-order, first-order, Higuchi equation, and Korsmeyer- Peppas equation) were applied to study drug release kinetics. Results: The addition of glycerol, glutaraldehyde, HPMC, and HPC polymers resulted in a considerable increase in the tensile strength and flexibility/elasticity of the hydrogel membranes. WVTR results suggest that hydrated hydrogel membranes can facilitate water vapor transfer. None of the hydrogel membranes supported microbial growth. HPMC-treated and HPC-treated hydrogel membranes allow slow, but sustained, release of gatifloxacin for 48 h. Drug release kinetics revealed that both diffusion and dissolution play an important role in gatifloxacin release. Conclusions: Given their physicochemical properties and gatifloxacin release pattern, HPMC-treated and HPC-treated hydrogel membranes exhibit effective and sustained drug release. Furthermore, HPMC-treated and HPC-treated hydrogel membranes possess physiochemical properties that make them effective and safe wound dressing materials.